Study on the mechanical failure of the cellulosic insulation of continuously transposed conductors in power transformers under the influence of short circuits and thermal ageing. (June 2021) - Oria, C.; Ferreño, D.; Carrascal, I.; Ortiz, A.; Fernández, I.
Highlights: Dielectric paper was mechanically characterised (in tensile, compressive and shear. The mechanical failure of the insulating paper used in the winding conductors. Electromagnetic forces was represented here through a radial bending force. Predictive models to estimate the lifespan of power transformers. Abstract: The dielectric paper of power transformers is subjected to ageing caused by high temperatures and chemical reactions in the dielectric oil. The electromagnetic forces that affect the conductor can cause the breakage of the paper and even the end of the useful life of the transformer. To improve the understanding of those phenomena, a continuously transposed conductor with four layers of dielectric paper (plain Kraft and crepe papers) was impregnated in naphthenic oil and aged during different periods, representative of its whole lifespan. Samples of the conductor were subjected to bending deformations compatible with a short circuit, and the cracks generated in the paper were analysed. The aged dielectric paper was mechanically characterised (in tensile, compressive and shear modes) and the bending tests of the conductors were simulated in ANSYS Static Structural, to estimate the strains in the paper. The Norris failure criterion was modified to predict the regions in the dielectric paper susceptible to fail for a particular ageing state and deformation level, obtaining a good agreement with the experimental results and thus validating this new version of the Norris approach.